PRISON PENALTY AS ADDITIONAL CRIMINAL SANCTION FOR SUBSTITUTION IN CORRUPTION CASE - Greafik Loserte; HM Said Karim; Amir Ilyas (Surakarta Law and Society Journal, 2018)
Criminal sanctions for replacement payments are a consequence of corruption corruption. The imprisonment as a substitute for the replacement money does not contain a consistent measure of one case to another, so the disparity of the decision is very potential. This type of research is a normative legal research, which is focused to examine the rules or norms in positive law. The approach used in this approach. The results of the criminal sanction of substitute money in corruption in the Indonesian legislation system are not regulated expressive verbis. In addition, the concept and application of replacement money to corruption also varies at different levels of the court, resulting in legal uncertainty and unfairness. Keywords: Criminal Sanctions; Replacement Money; Corruption Crime